Active Targeting of P-Selectin by Fucoidan Modulates the Molecular Profiling of Metastasis in Docetaxel-Resistant Prostate Cancer - Chang-Hsun Ho; Mei-Lin Chen; Hau-Lun Huang; Chih-Jen Lai; Chih-Hsin Liu; Chih-Pin Chuu; Yu-Hsin Lin (Marine Drugs, 2022)
The standard of care for prostate cancer (PCa) is androgen deprivation therapy (ADT). Although hormone-sensitive PCa is curable by ADT, most conditions progress to castration-resistant prostate cancer (CRPCa) and metastatic CRPCa (mCRPCa). Front-line docetaxel has been administered to patients with CRPCa and mCRPCa. Nevertheless, docetaxel resistance after half a year of therapy has emerged as an urgent clinical concern in patients with CRPCa and mCRPCa. We verified the mechanism by which docetaxel-resistant PCa cells (DU/DX50) exhibited significant cell migration and expression of malignant tumor-related proteins. Our study shows that the biological activity of fucoidan has an important application for docetaxel-resistant PCa cells, inhibiting IL-1R by binding to P-selectin and reducing the expression levels of NF-κB p50 and Cox2 in this metastasis-inhibiting signaling pathway. Furthermore, the combined treatment of fucoidan and docetaxel showed significant anticancer and synergistic effects on the viability of DU/DX50 cells, which is relevant for overcoming the current limitations and improving treatment outcomes. Overall, fucoidan-based combination chemotherapy may exert beneficial effects and facilitate the treatment of docetaxel-resistant PCa.